2011
DOI: 10.1177/1748895811419972
|View full text |Cite
|
Sign up to set email alerts
|

Different yet complementary: Two approaches to supporting victims of sexual violence in the UK

Abstract: This article explores the strengths and limitations of two different types of settings that provide specialist support to victims of sexual violence in the UK: Sexual Assault Referral Centres (SARCs) and voluntary sector organizations such as Rape Crisis. Qualitative data from six case study sites and quantitative data from 35 sexual violence projects in England and Wales revealed that the type of setting affected the types of referrals received and this, in turn, shaped the services required by victims and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…Of the 107 papers included in the review, some were relevant to more than one of our three review questions. For review question one, we included 78 publications providing information on how sexual assault services address mental health and substance misuse [20, 24-26, 33-106]; for review question two, we included 6 papers of five trial evaluations [84,89,92,[107][108][109]; and for review question three, we included 34 studies on stakeholders' views [20,25,34,37,44,53,54,60,62,72,78,82,86,90,93,94,97,[110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] and 10 policy documents [20,22,[127][128][129][130][131][132]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 107 papers included in the review, some were relevant to more than one of our three review questions. For review question one, we included 78 publications providing information on how sexual assault services address mental health and substance misuse [20, 24-26, 33-106]; for review question two, we included 6 papers of five trial evaluations [84,89,92,[107][108][109]; and for review question three, we included 34 studies on stakeholders' views [20,25,34,37,44,53,54,60,62,72,78,82,86,90,93,94,97,[110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] and 10 policy documents [20,22,[127][128][129][130][131][132]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…We found 34 papers [20,25,34,37,44,53,54,60,62,72,78,82,86,90,93,94,97,[110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] relating to 32 studies, which reported stakeholders' views on how sexual assault services should identify and respond to mental health and substance misuse problems for people following sexual assault. Twenty five were peer-reviewed publications [25,34,44,53,54,60,72,78,82,90,94,[110][111][112][113][114]…”
Section: Q3: Studies On Stakeholders' Viewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rape crisis centers (RCCs) have provided vital support to sexual assault survivors since they were established in the United States in the 1970s via grassroots efforts to combat an oppressive patriarchal culture (Campbell & Martin, ; Maier, ; Robinson & Hudson, ). RCCs are often the frontline of services for survivors, providing crisis intervention (e.g., crisis hotline), medical and legal advocacy, and counseling services through a multidisciplinary team that often includes professionals and volunteers (Baker & Bevacqua, ; Campbell & Martin, ).…”
mentioning
confidence: 99%